2013
DOI: 10.1111/eff.12114
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Galaxias platei in a depauperate lake

Abstract: Galaxias platei is widespread and common in southern South America, but its ecology is poorly documented relative to other native species, especially those of commercial importance. Galaxias platei occurs across a large range of environmental conditions, including hydrologically isolated, high‐elevation lakes. Consequently, there were several lakes in the Patagonian region where it was the only native fish species. Introduction of salmonids into almost all lakes in Patagonia where G. platei occurs has potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…This suggests that adults of P. trucha do not recognise conspecific juveniles as potential prey. This finding is contrasting with recent studies from other monospecific lake in Patagonia inhabited by galaxiid G. platei (Thompson lake, Aysen River Basin), where rapid ontogenetic trophic scaling was found in early developmental stages due to cannibalism (Belk et al, 2014). Populations of P. trucha inhabiting these small lakes (Silvia and Maldonado) seem to represent a different dynamic, more similar to stunted populations (sensu Ylikarjula et al, 1999).…”
Section: Trophic Ecology Of P Trucha In Isolationcontrasting
confidence: 77%
See 1 more Smart Citation
“…This suggests that adults of P. trucha do not recognise conspecific juveniles as potential prey. This finding is contrasting with recent studies from other monospecific lake in Patagonia inhabited by galaxiid G. platei (Thompson lake, Aysen River Basin), where rapid ontogenetic trophic scaling was found in early developmental stages due to cannibalism (Belk et al, 2014). Populations of P. trucha inhabiting these small lakes (Silvia and Maldonado) seem to represent a different dynamic, more similar to stunted populations (sensu Ylikarjula et al, 1999).…”
Section: Trophic Ecology Of P Trucha In Isolationcontrasting
confidence: 77%
“…Trophic ecology of P. trucha is still less understood in lakes of western Patagonia. In many of these lakes, G. platei has been described as the native top predator Belk et al, 2014) and its trophic scaling was reported as it shifts from zooplanktivory at small sizes to cannibalistic piscivory at larger sizes (Belk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Eggs are thus unlikely to be dispersed across lakes. Larvae generally reside in the limnetic zones, and adults are generally found most abundantly near the benthos from where they move into shallow areas to feed on macroinvertebrates, eggs and small fish, including G. platei individuals (Barriga et al 2002;Belk et al 2014). The IBD pattern we have observed in G. platei is thus most likely explained by a process of isolation by dispersal limitation (IBDL, Orsini et al 2013).…”
Section: Isolation By Distancementioning
confidence: 74%
“…; Belk et al . ). The IBD pattern we have observed in G. platei is thus most likely explained by a process of isolation by dispersal limitation (IBDL, Orsini et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation